Elements of Orientalism as a Socio-Historical Literary Translation Model: Tracing Sa’di in European Renditions - Kharmandar, Mohammad Ali; Nematollahi, Fatemeh (Iranian Journal of Translation Studies, 2015)
Over the past five centuries, the West has experienced parallel yet integrated developments that have led to profound asymmetries in world histories. Colonial ideology, coupled with a (pseudo)scientific anthropological and ethnographical underpinning, has resulted in the establishment of disciplines such as Orientalism which positively or negatively “represent” or “translate” the Eastern world within a Eurocentric paradigm. The purpose of this study is to propose a causal holistic socio-historical literary model of Orientalist translation. Primarily, the theoretical foundations of the study are explored, and then an actual condensed literary history (European renditions of Sa’di) is presented. Following an intensive comparison of theoretical considerations and the actual sample, four elements are extracted: scholarly agency, continental translation, industrial/scientific superiority of Orientalists, and literary richness of Eastern cultures. The study proposes implications and suggestions that contribute to, among others, philosophy of history and translation, critical Occidentalism, comparative literature, and Persian Translation Paradigm.